2022
DOI: 10.1039/d2ta02584a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and electronic structure engineering of transition metal nitrides for supercapacitor applications

Abstract: Supercapacitors are among the most promising energy storage devices; Supercapacitor exhibits a larger power density than batteries, but they remain challenging a poor energy density. To meet the ever-increasing demands...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 118 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…This densely grown nanostructure has a large surface area, which can provide a high energy storage capacity through a sufficient oxidation reaction. 61 This thick nanosheet showed excellent cycle stability owing to its stable structure (Fig. 3f ).…”
Section: Composition and Morphology Analysismentioning
confidence: 95%
“…This densely grown nanostructure has a large surface area, which can provide a high energy storage capacity through a sufficient oxidation reaction. 61 This thick nanosheet showed excellent cycle stability owing to its stable structure (Fig. 3f ).…”
Section: Composition and Morphology Analysismentioning
confidence: 95%
“…Pseudocapacitive materials coupled with high surface area carbon materials exhibited larger energy density while maintaining a high power density. [11][12][13][14][15][16][17] However, it still remains important to develop an alternative strategy to increase the performance of micro-supercapacitors by considering the geometrical parameters of the microelectrode in addition to the preferred electrode material. In this direction, Wang et al, 18 Liu et al 19 and Kim et al 20 reported higher performance in microsupercapacitors aer optimization of electrode patterns.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid depletion of fossil fuels, the ever-increasing demand for energy consumption has stimulated the scientific community to explore new environmentally friendly and sustainable energy sources. , Energy storage and energy conversion technologies such as rechargeable batteries, water electrolyzers, supercapacitors, etc. are renowned environmentally sustainable energy sources.…”
Section: Introductionmentioning
confidence: 99%